Research on the Management of Sports Events in the Context of Sports Tourism - Liu, Gang; Li, Hailin; Feng, Xiaodong (Transactions on Economics, Business and Management Research, 2024)
This article first analyzes the management significance of sports events in the context of sports tourism from the perspectives of increasing urban attractiveness, optimizing industrial structure, increasing employment opportunities, improving urban infrastructure, increasing economic benefits, and improving the quality of public services. Then it elaborates on management strategies for sports events in the context of sports tourism from the perspectives of competition management, information communication, cost control, risk control, logistics management, and evaluation management. Finally, it proposes management directions for sports events in the context of sports tourism from the perspectives of developing a whole-area tourism strategy, combining sports events with tourist attractions, improving the institutional guarantee of sports tourism, and strengthening the promotion and publicity of sports tourism.